Photocatalytic Dehydrogenative Cross‐Coupling of Alkenes with Alcohols or Azoles without External Oxidant. (19th December 2016) - Yi, Hong; Niu, Linbin; Song, Chunlan; Li, Yiying; Dou, Bowen; Singh, Atul K.; Lei, Aiwen
Abstract: Direct cross‐coupling between alkenes/R‐H or alkenes/RXH is a dream reaction, especially without external oxidants. Inputting energy by photocatalysis and employing a cobalt catalyst as a two‐electron acceptor, a direct C−H/X−H cross‐coupling with H2 evolution has been achieved for C−O and C−N bond formation. A new radical alkenylation using alkene as the redox compound is presented. A wide range of aliphatic alcohols—even long chain alcohols—are tolerated well in this system, providing a new route to multi‐substituted enol ether derivatives using simple alkenes. Additionally, this protocol can also be used for N ‐vinylazole synthesis. Mechanistic insights reveal that the cobalt catalyst oxidizes the photocatalyst to revive the photocatalytic cycle.